2012
DOI: 10.1016/j.tourman.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Do expectations of future wealth increase outbound tourism? Evidence from Korea

Abstract: a b s t r a c tAs international tourism is generally considered a luxury good, models to date have shared an understanding that demand is dependent on discretionary income. However, consumption theories predict that a shift in demand can be induced without changes in actual earnings when expectations for future income are adjusted. This presumes demand for international tourism can be influenced by "wealth effects" from real estate and financial assets. This study tested for the wealth effect on Korean outboun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 43 publications
4
33
0
1
Order By: Relevance
“…This is in line with previous studies on determinants of outbound tourism (e.g. Kim et al, 2012;Lim, 1997). In addition, we found that the coefficient of travel costs is negative but is not statistically significant in the full sample of countries, developed countries and developing economies.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with previous studies on determinants of outbound tourism (e.g. Kim et al, 2012;Lim, 1997). In addition, we found that the coefficient of travel costs is negative but is not statistically significant in the full sample of countries, developed countries and developing economies.…”
Section: Resultssupporting
confidence: 92%
“…Thus, following existing studies on outbound tourism, income, exchange rate and travel costs were selected as control variables in the model specification. Income level in the origin country has been found to be an important explanatory variable that explains overseas travel (particularly for leisure purpose) because overseas travel is expensive and is generally regarded as a luxury good (Kim et al, 2012;Lim, 1997). It is to be expected that income influences the demand for outbound tourism positively.…”
Section: Variables and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Such a proposition is consistent with the findings of Kim et al (2012) in relation to outbound tourism in Korea. Thus, we posit the first testable hypothesis:…”
Section: Consumer Sentiment and Tourism Demandsupporting
confidence: 91%
“…The results of the study show that the international tourism demand by South Korea is both income elastic and price elastic. Kim et al (2012) examined the Korean household asset effects on outbound travelling and their findings show the possibility of a significant wealth effect from housing on the outbound travel demand, but not from the financial assets. Che (2013) investigated the Taiwanese outbound tourism and the results show that a destination country's consumer price index (CPI) has a positive linear relation with the number of Taiwanese people travelling abroad.…”
Section: Literature Reviewmentioning
confidence: 99%